The need of tree tenure security to maintenance the Traditional Agroforestry (Parak) In Koto Malintang Village, West Sumatra - Tri Martial (Syiah Kuala University, 2012)
Communal forests in Indonesia, especially in the form of agroforestry commonly undeveloped and almost in traditional management. In Koto Malintang, West Sumatra agroforestry practice known as ‘parak’ has existed since decades ago. This study aims to determine the importance of tree tenure security in the ‘parak’ management for its sustainability in Koto Malintang, West Sumatra. The research uses descriptive method to identify the tree tenure security. Gambaran jaminan status penguasaan tanah dan pohon, serta kebijakan pemerintah yang telah dikeluarkan dalam bentuk undang-undang dan peraturan yang berkaitan dengan hak-hak dalam kerangka penguasaan tanah dan pohon secara luas. Dalam penelitian ini menggunakan strategi pendekatan sebagai berikut: Pertama penelitian melakukan observasi untuk menilai dan menggambarkan pola-pola penguasaan pohon pada berbagai penguasaan tanah pada tanah komunal dan tanah negara yang mengacu kepada Rapid appraisal social forestry for land and tree tenure (FAO, 1989). To assess and describe patterns of tree control on communal land which refers to the Rapid appraisal of social forestry for land and tree tenure. Kedua menilai status jaminan hak-hak masyarakat pada penguasaan tanah dan penguasaan pohon dengan pendekatan terhadap hak-hak yang terdapat pada tanah dan pohon. The findings indicate lack of tree tenure security, especially for the purpose of selling the trees. Communal rights limit the freedom of timber use in an uncontrolled manner. But the communal rights maintain the system sustainability that is practiced as local institutional rules. For the income purposes, farmers tend to avoid planting timber-producing trees and prioritizing to quickly produce an annual crop. This is due to the limited of tenure security encourages reluctance of trees planting. Planting more trees is caused by timber interests. Planting trees is caused by the communal interest to the trees benefit for environmental sustainability.